Effect of Reward and Punishment on Employee Performance (Study at CV. Barokah Maju Jaya Makmur, Sidoarjo City) - WIDIANINGTYA, ALVIERA MAYASISTA (Jurnal Ilmiah Mahasiswa FEB, 2019)
This study aims to examine the effect of rewards and punishments on the performance of CV employees. Barokah Maju Jaya Makmur which is located onJalan Raya Taman Bunga, Tropodo Village, Waru District, Sidoarjo Regency,East Java. This type of research is quantitative. From the hypothesis testconducted, this study obtained results that reward and punishment have a positiveand significant effect on employee performance on CV. Barokah Maju JayaMakmur. Keywords: Reward, Punishment, and Employee Performance